“The Devil Made Me Do It.” Popular Spirituality in a Rural Québec Parish, 1736–1901 - Abbott, Frank (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
This paper examines popular tales involving the Devil in the rural Québec parish of St-Joseph-de-Beauce, 70 kilometers southeast of Québec City. A microhistorical examination of the interaction between popular beliefs and clerical discourse in the parish over an extended period of time offers valuable insights into the functional details of the relationship between parishioners and curés that might otherwise be missed, misinterpreted, or even invisible at the diocesan level. Popular stories about Satan in Beauce County reveal how Catholicism intersected with popular belief systems in rural Québec. On the one hand, people’s fear of the Devil reinforced the clerical message that their spiritual needs took precedence over the inclinations of their bodies. But people also produced their own versions of the clergy’s construction of the Devil, and added content which often differed from the clerical version of Satan. Understanding the popular views of the Devil sheds more light on the ways that orthodox Catholic belief became blended with popular customs and tales, as well as how ordinary Catholics responded to the Church’s messages from the pulpit and in the confessional (or why they did not).